Pertumbuhan Perusahaan, Financial Distress, Dan Kualitas Audit Terhadap Opini Audit Going Concern - Alfira Lutfianah; Rananda Septanta (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the effect of company growth, financial distress, and audit quality on going concern audit opinions in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach using a purposive sampling method, resulting in 43 companies with a total of 258 observation data points. The data were analyzed using logistic regression with EViews 12 software. The results indicate that company growth and financial distress significantly affect going concern audit opinions, while audit quality does not have a significant effect. Simultaneously, company growth, financial distress, and audit quality influence going concern audit opinions. These findings suggest that a company’s financial condition and growth capability play a crucial role in auditors’ assessments of business continuity.